Dose-Dependency of Resveratrol in Providing Health Benefits - Subhendu Mukherjee; Jocelyn I. Dudley; Dipak K. Das (2010)
This review describes the dose-dependent health benefits of resveratrol, a polyphenolic antioxidant that is found in a variety of foods, especially grape skin and red wine. Resveratrol provides diverse health benefits including cardioprotection, inhibition of low-density lipoprotein, activation of nitric oxide (NO) production, hindering of platelet aggregation [32] A.A.E. Bertelli, D.E. Giovannini, R.L. Caterina, W. Bernini, M. Migliori and M. Fregoni et al., Antiplatelet activity of cis-resveratrol, Drugs Exp Clin Res 22 (1996), pp. 61-63. View Record in Scopus | Cited By in Scopus (111) and promotion of anti-inflammatory effects. Studies have shown that at a lower dose, resveratrol acts as an anti-apoptotic agent, providing cardioprotection as evidenced by increased expression in cell survival proteins, improved postischemic ventricular recovery and reduction of myocardial infarct size and cardiomyocyte apoptosis and maintains a stable redox environment compared to control. At higher dose, resveratrol acts as a pro-apoptotic compound, inducing apoptosis in cancer cells by exerting a death signal. At higher doses, resveratrol depresses cardiac function, elevates levels of apoptotic protein expressions, results in an unstable redox environment, increases myocardial infarct size and number of apoptotic cells. At high dose, resveratrol not only hinders tumor growth but also inhibits the synthesis of RNA, DNA and protein, causes structural chromosome aberrations, chromatin breaks, chromatin exchanges, weak aneuploidy, higher S-phase arrest, blocks cell proliferation, decreases wound healing, endothelial cell growth by fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor, and angiogenesis in healthy tissue cells leading to cell death. Thus, at lower dose, resveratrol can be very useful in maintaining the human health whereas at higher dose, resveratrol has pro-apoptotic actions on healthy cells, but can kill tumor cells.